Estilos de aprendizaje en relación con las áreas del conocimiento de los estudiantes de la Universidad de la Costa en la ciudad de Barranquilla (2021)
The learning process and learning styles have been the focus of interest for a long time, therefore, the present research aims to analyze the learning styles in relation to the areas of knowledge of the students of the Universidad De La Costa, in the city of Barranquilla. For this purpose, a quantitative research of descriptive transversal character is carried out, where the sample was non-probabilistic including 1874 participants of the research. It was found that 52.93% of the participants are from the area of economics, administration, accounting and related areas, and 62.86% of the students have a predominant visual style. On the other hand, by means of a multivariate factor analysis (MANOVA) it is possible to identify that significant differences are only present in the auditory style between the areas of social sciences, humanities and education, and those of engineering, architecture, urban planning and related areas. Thus, it is concluded that there is no relationship between the area of knowledge and the learning style, which is evidenced by the absence of significant differences in the analysis of means.